Pengaruh Desa Wisata Terhadap Peningkatan Ekonomi Lokal di Desa Tenjolaya Kecamatan Pasirjambu Kabupaten Bandung - Riska Apriliani; Oman Sukirman; Rifqi Asy’ari (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study shows that the development of tourism villages in Tenjolaya Village has had a positive impact on improving the local economy. Key findings include increased economic activity through business opportunities, employment, increased community income, and increased tourist visits. The condition of the tourism villages, assessed as good in terms of attractions, accessibility, amenities, and institutions, demonstrates that destination management has been able to support tourism activities optimally. The analysis also indicates a strong relationship between tourism villages and local economic growth, confirming that the village tourism sector can be a driver of the community's economy. However, the contribution of tourism villages to the local economy is not yet fully dominant because there are still other factors that influence community economic growth. The implications of these findings indicate that tourism village development needs to be supported by strengthening infrastructure, improving the quality of tourism services, empowering local communities, and collaboration between the government, tourism managers, and the community to ensure optimal and sustainable economic benefits.